Antifouling paint booster biocides (Irgarol 1051 and diuron) in marinas and ports of Bushehr, Persian Gulf. Issue 1 (15th April 2016) - Saleh, Abolfazl; Molaei, Saeideh; Sheijooni Fumani, Neda; Abedi, Ehsan
Abstract: In the present study, antifouling paint booster biocides, Irgarol 1051 and diuron were measured in ports and marinas of Bushehr, Iran. Results showed that in seawater samples taken from ports and marinas, Irgarol was found at the range of less than LOD to 63.4 ng L − 1 and diuron was found to be at the range of less than LOD to 29.1 ng L − 1 (in Jalali marina). 3, 4-dichloroaniline (3, 4-DCA), as a degradation product of diuron, was also analyzed and its maximum concentration was 390 ng L − 1 . Results for analysis of Irgarol 1051 in sediments showed a maximum concentration of 35.4 ng g − 1 dry weight in Bandargah marina. A comparison between the results of this study and those of other published works showed that Irgarol and diuron pollutions in ports and marinas of Bushehr located in the Persian Gulf were less than the average of reports from other parts of the world. Highlights: Irgarol and diuron were measured in ports and marinas of Bushehr, Iran. Irgarol and diuron were detected in 31 and 25% of water samples, respectively. Higher presence of biocides in dhows mooring spaces was observed. The area's sediments and water are characterized by low levels of antifoulants.